2021
DOI: 10.1021/acsami.1c07490
|View full text |Cite
|
Sign up to set email alerts
|

Effective Solid Electrolyte Interphase Formation on Lithium Metal Anodes by Mechanochemical Modification

Abstract: Lithium metal batteries are gaining increasing attention due to their potential for significantly higher theoretical energy density than conventional lithium ion batteries. Here, we present a novel mechanochemical modification method for lithium metal anodes, involving roll-pressing the lithium metal foil in contact with ionic liquid-based solutions, enabling the formation of an artificial solid electrolyte interphase with favorable properties such as an improved lithium ion transport and, most importantly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…On the other hand, recent work reporting the formation of an artificial SEI layer on Li metal via decomposition of C 3 mpyrFSI proposed the stable formation of SO 2 NSO 2 F along with LiF, which forms from the first decomposition step of the FSI anion with the loss of a fluorine. 43 Whereas early work from Budi et al 44 suggested that the species is unstable, it is possible that in the presence of a high sodium ion concentration an insoluble Na 2 [SO 2 N-SO 2 F] species could also form. Since both of these complexes are chemically very similar, 23 Na NMR would be unable to differentiate them.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recent work reporting the formation of an artificial SEI layer on Li metal via decomposition of C 3 mpyrFSI proposed the stable formation of SO 2 NSO 2 F along with LiF, which forms from the first decomposition step of the FSI anion with the loss of a fluorine. 43 Whereas early work from Budi et al 44 suggested that the species is unstable, it is possible that in the presence of a high sodium ion concentration an insoluble Na 2 [SO 2 N-SO 2 F] species could also form. Since both of these complexes are chemically very similar, 23 Na NMR would be unable to differentiate them.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The latter complex has been proposed to form by the reaction of FSI with OH– that may be present on the native Na metal SEI or form from water reduction. On the other hand, recent work reporting the formation of an artificial SEI layer on Li metal via decomposition of C 3 mpyrFSI proposed the stable formation of SO 2 NSO 2 F along with LiF, which forms from the first decomposition step of the FSI anion with the loss of a fluorine . Whereas early work from Budi et al suggested that the species is unstable, it is possible that in the presence of a high sodium ion concentration an insoluble Na 2 [SO 2 N-SO 2 F] species could also form.…”
Section: Resultsmentioning
confidence: 99%
“…Various strategies, including developing advanced electrolytes, , constructing artificial solid electrolyte interphase (SEI) layers, , current collector engineering, and so forth, , have been proposed to resolve the problems of lithium-metal anodes (LMAs) and improve the CE of Li-metal-based batteries (LMBs). Among these strategies, anode current collector engineering plays a critical role in regulating the lithium deposition and stripping process and improving the CE, especially in a lean LMA or an anode-free lithium-metal battery structure where lithium directly deposits on the current collector .…”
Section: Introductionmentioning
confidence: 99%
“…4−6 The highly reactive Li metal is accompanied by some severe problems, such as the growth of lithium dendrites, 7 huge volume expansion/contraction during the charge/discharge process, and continuous side reactions between the electrolyte and lithium, resulting in low Coulombic efficiency (CE) and limited cycle life of batteries. 8 Various strategies, including developing advanced electrolytes, 9,10 constructing artificial solid electrolyte interphase (SEI) layers, 11,12 current collector engineering, and so forth, 13,14 have been proposed to resolve the problems of lithium-metal anodes (LMAs) and improve the CE of Limetal-based batteries (LMBs). Among these strategies, anode current collector engineering plays a critical role in regulating the lithium deposition and stripping process and improving the CE, especially in a lean LMA or an anode-free lithium-metal battery structure where lithium directly deposits on the current collector.…”
Section: Introductionmentioning
confidence: 99%
“…7b). As Li 2 O belongs to the solid electrolyte interphase (SEI) with favorable properties such as an improved lithium-ion transport, 47–51 the lithium-ion migration barriers in Li 2 O remain higher than barriers in LLZTO. The lithium-ion migration barriers from position 9 to position 10 and from position 10 to position 9 in La 2 Zr 2 O 7 are 2.48 eV and 5.23 eV, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%